FINANCING OF THE SYSTEM OF HIGHER EDUCATION AS THE MAIN FACTOR OF HUMAN CAPITAL DEVELOPMENT - Mukhtаrovа Indirа Yаshаrbek Kizi (Journal Park Publishing, 2023)
This article discusses the priority aspects of public financing of the higher education system and analyzes the level of public funding of the higher education system in the Republic of Uzbekistan. It also studies how higher education is financed in the developed countries of the world and how it affects the potential of staff. The modernization of education is singled out in the article as one of the most urgent problems of the modern socio-economic development of Uzbekistan. Recommendations are offered to achieve the required level of funding for educational institutions: creation of a trust fund for the development of education; creation of a larger information base in this area; providing banks working in the field of education lending with tax incentives to encourage their activities in this area; providing financial assistance in the form of scholarships or other payments to student activists, excellent students, low-income students, even if they study on commercial terms; providing a discount to students in case of early payment of tuition.
Keywords: financing of education, services of higher professional education, educational credit, state guarantees.